Cybercrime: Analisis Dan Mitigasi Resiko Penipuan Tilang Online Melalui Aplikasi WhatsApp (WA) - Hafiz Rahmadani, Fayza; Cahya Sutany, Hendrian; Ragil Aditya, Mohamad; Adita Fajar, Muhammad; Ulan Dari, Yesika; Fauziyah (Jurnal Sistem Informasi Galuh, 2025)
Online ticket fraud via WhatsApp is a crime that is troubling and detrimental to society. Online ticket scams that have been rampant lately have become an increasingly serious threat in today's digital era and have caused losses to victims, one of which is financial loss due to online ticket scams. Therefore, prevention and mitigation efforts are very important to protect the public from this fraud mode. The importance of increasing public education and literacy about online fraud, increasing cyber patrols and law enforcement against online fraud perpetrators can be a solution to prevent online ticket fraud via WhatsApp. This research was conducted to increase public awareness about information security by conducting continuous analysis and education, it is hoped that online fraud can be minimized and the public can avoid losses, understand the mode of online ticket fraud via WhatsApp, and develop effective prevention strategies for online ticket fraud that is rampant. The National Cyber and Crypto Agency related to cybercrime, public complaints as many as 1,216 in 2023, it can be concluded that in Indonesia cybercrime or online fraud often occurs among the public.